catena-Poly[[bis(1-methyl-1H-imidazole-κN3)zinc]-μ-3-nitrophthalato-κ2O1:O2] - Ming-Lin Guo; Xi-Juan Zhang (Acta Crystallographica Section E, 2012)
In the title complex, [Zn(C8H3NO6)(C4H6N2)2]n, the carboxylate groups of the 3-nitrophthalate dianion ligand coordinate the ZnII ion in a bis-monodentate mode. The ZnII ion shows distorted tetrahedral coordination as it is bonded to two O atoms from the carboxylate groups of symmetry-related 3-nitrophthalate anions and two N atoms of two independent 1-methylimidazole molecules. The bridging 3-nitrophthalate ligand allows the formation of one-dimensional chains in the c direction. The crystal structure is further stabilized by weak intermolecular C—H...O hydrogen bonds.